Research notes from interview in Bayankhongor aimag, March 13, 2022 (Mobilities and Socialities: COVID-19 in the Drylands of Africa and Beyond, 2022)
Includes: Text message sent by co researcher from Bayankhongor aimag (March 20)
Keywords: Arid regions; Prices; Households; Travel; Labor; Festivals; Lockdown; Tsagaan Sar; International Trade; Mongolia; Mobility; COVID-19 Pandemic